2015
DOI: 10.17795/jhealthscope-25344
|View full text |Cite
|
Sign up to set email alerts
|

The Quality Gap in the Services Provided by Rural Maternity Units in Southeast of Iran

Abstract: Background:Providing high-quality maternity services is crucial to increase utilization of these services and reduce maternal mortality. The quality of the maternity services provided to pregnant women in rural areas of Iran is poorly understood. Objectives: This study aimed to investigate the quality gap in the maternity care services provided by Rural Delivery Facilities and Safe Delivery Posts in Sistan and Balouchestan Province, southeast of Iran, as expressed by the difference in women's perceptions and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…Although it was anticipated that there would be significant differences in perceptions of quality of care between vulnerable and non-vulnerable groups, there were in fact only a limited number of differences reported between women with and without disabilities, and even fewer between Dalit and non-Dalit women. The study found fewer associations between socio-demographic factors and perceived quality of care than studies in other settings [ 46 , 47 ]. However, it is important to note that all groups rated many aspects of care very low and thus the findings in this study reflect overall dissatisfaction with the quality of care.…”
Section: Discussioncontrasting
confidence: 68%
“…Although it was anticipated that there would be significant differences in perceptions of quality of care between vulnerable and non-vulnerable groups, there were in fact only a limited number of differences reported between women with and without disabilities, and even fewer between Dalit and non-Dalit women. The study found fewer associations between socio-demographic factors and perceived quality of care than studies in other settings [ 46 , 47 ]. However, it is important to note that all groups rated many aspects of care very low and thus the findings in this study reflect overall dissatisfaction with the quality of care.…”
Section: Discussioncontrasting
confidence: 68%
“…Previous studies found the largest gaps in responsibility (22,23) and reliability (24,25). In contrast, some studies found the smallest gap in responsibility (26) and reliability (27). This dissimilarity can be caused by those different characteristics of patients, different facilities of health organizations, and the diverse nature of services.…”
Section: Discussionmentioning
confidence: 92%
“…Results of a study conducted in the city of Qazvin in Iran with regard to quality health services in 2014 revealed that, from the perspective of people in Qazvin (Iran), there was a gap in health quality of organizations providing health services in this province; however, there was no study conducted for comparison between public and private sectors in Qazvin Province ( 15 ). Tabatabai’s study also showed a quality gap in health services, and patients’ expectations were not met adequately ( 16 ). Evaluating quality of health services provided to patients and their perception of services as well as identifying factors influencing their perception is among the main criteria of a health system.…”
Section: Introductionmentioning
confidence: 99%